Uric Acid Response To Different Intensities Of Training In Amateur Footballers: Findings From A Randomized Control Study - Naseem Ullah, Dr. Wasim Khan, Dr. Syed Asif Abbas, Salma Faiz, Muhammad Shehzad (Migration Letters, 2024)
Main Purpose: This study examined the effects of training intensity on uric acid levels among football players to understand its implications for oxidative stress and performance. Methods: A total of 80 football players were randomly assigned to either a low intensity exercise (n=20), moderate intensity exercise (n=20) and high-intensity (n = 20) or control group (n = 20. Uric acid levels were measured before and after a 12-week training period. Descriptive statistics, independent samples t-tests, ANOVA, and correlation analyses were employed to analyze the data. Results: The high-intensity training group had a significantly higher mean uric acid[1] level (6.5 mg/dL, SD = 1.2 mg/dL) compared to the moderate-intensity group (5.2 mg/dL, SD = 1.0 mg/dL). Independent samples t-tests revealed a significant difference between the groups (t(58) = 3.45, p < 0.01), with an effect size of Cohen’s d = 0.89, indicating a large effect. ANOVA showed a significant main effect of training intensity on oxidative stress markers (F(1, 58) = 12.78, p < 0.01). Pearson correlation analysis demonstrated a positive relationship between training intensity and uric acid levels (r = 0.62, p < 0.01). Multiple regression analysis confirmed that training intensity was a significant predictor of uric acid levels (β = 0.45, p < 0.01). Conclusion: The study provides evidence that higher training intensity is associated with increased uric acid levels, suggesting that intense training regimens may elevate oxidative stress. These findings underscore the importance of monitoring uric acid levels to manage potential oxidative stress in athletes undergoing high-intensity training.